Critical issues on changing dynamics in employee relations and workforce diversity - Yadav, Radha, 1988-; Panday, Priyanka, 1989-; Sharma, Naman, 1986- (Advances in human resources management and organizational development (AHRMOD) book series., 2021)
"This book addresses the challenges and issues pertaining to the changing dynamics of employee relations and provides additional support to better deal with critical issues related to people management"--